Optimum Temperature for Drying Process of Okra Fruit - Benchasri, Sorapong; Juthong, Thidarat (Journal of Vocational Education in Agriculture, 2023)
The okra (KN-OYV-02) were planted at the Faculty of Technology and Community Development, Phatthalung campus, Thaksin University for studying the appropriate conditions for okra blanching and drying process. Okra blanching methods, immersion in water and in boiling water with ascorbic acid (0, 1 and 2%) for 0, 2, 4 and 6 minutes, were compared. Blanching in boiling water for 4 mins without ascorbic acid preserved green color of okra. The okra showed yellow-brown color when blanching in boiling water with ascorbic acid. Subsequently, drying temperatures of hot-air dryer were observed at 60, 65 and 70 °C. Drying time was determined when water activity of okra was less than 0.6. Drying time decreased with an increase in drying temperature. Drying temperature at 60-65 °C and at 70 °C took 16 hrs and 12 hrs, respectively. Therefore, drying temperature at 70 °C was appropriated for okra drying process due to the short duration and maximum drying rate. In addition, L* and b* values of dried okra were decreased due to blanching and drying process but a* value of dried okra was increased when compared with fresh okra.